2022
DOI: 10.1186/s12974-022-02393-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from bone-marrow mesenchymal stem cells alleviate cognitive decline in AD-like mice by improving BDNF-related neuropathology

Abstract: Background Alzheimer's disease (AD) is a neurodegenerative disease characterized by a progressive decline in cognitive ability. Exosomes derived from bone-marrow mesenchymal stem cells (BMSC-exos) are extracellular vesicles that can execute the function of bone-marrow mesenchymal stem cells (BMSCs). Given the versatile therapeutic potential of BMSC and BMSC-exos, especially their neuroprotective effect, the aim of this study was to investigate the potential effect of BMSC-exos on AD-like behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 69 publications
0
55
0
Order By: Relevance
“…Nevertheless, PP‐based isolation kits as ExoQ (Aulston et al, 2019; Ding et al, 2018; Guo et al, 2020; Park et al, 2020; Wang et al, 2012) and TEI (Lee et al, 2022; Liu et al, 2022; Marzano et al, 2019; Ozansoy et al, 2020; Peng et al, 2022; Tang et al, 2022) are also being employed in some studies, as well as UF kit Exo:pure (Zhdanova et al, 2021). To note, the employment of different methods for EVs isolation from diverse cell lines render in different results.…”
Section: Methodologies Employed In Evs Isolation From Ad and Pd Mimic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, PP‐based isolation kits as ExoQ (Aulston et al, 2019; Ding et al, 2018; Guo et al, 2020; Park et al, 2020; Wang et al, 2012) and TEI (Lee et al, 2022; Liu et al, 2022; Marzano et al, 2019; Ozansoy et al, 2020; Peng et al, 2022; Tang et al, 2022) are also being employed in some studies, as well as UF kit Exo:pure (Zhdanova et al, 2021). To note, the employment of different methods for EVs isolation from diverse cell lines render in different results.…”
Section: Methodologies Employed In Evs Isolation From Ad and Pd Mimic...mentioning
confidence: 99%
“…The therapeutic potential of EVs has also been addressed using Yang et al, 2020), alleviated brain inflammation by modulating microglia and astrocytes activation (Ding et al, 2018;Liu et al, 2022), and improved spatial learning and memory function (Ding et al, 2018;Liu et al, 2022;Zhdanova et al, 2021). MSCderived EVs were also used as a drug delivery system of neprilysn (an Aβ degrading enzyme), causing improvements spatial memory ability, reducing hippocampus neuronal damage, senile plaques accumulation and alleviating brain inflammation in the AD rat model (Izadpanah et al, 2020).…”
Section: Stem Cellsmentioning
confidence: 99%
“…With well-characterized immunoregulatory neurotrophic and regenerative properties, MSC-derived exosomes were considered as a promising candidate for AD therapy and most widely studied. In mouse models, MSC-derived exosome administration via the lateral ventricle or intravenous injection could reduce Aβ expression and improve AD-like behaviors (Chen et al, 2021 ; Liu et al, 2022 ). Enzymatically active neprilysin, the most important Aβ-degrading enzyme in the brain, is also found in MSC-derived exosomes (Joshi et al, 2015 ).…”
Section: Exosomes Derived From Different Cells Play Different Roles I...mentioning
confidence: 99%
“…Neuroinflammation is a contributing factor for many neuropsychiatric diseases including Alzheimer’s disease and depression ( Fang et al, 2020 ; Qi et al, 2021 ; Liu S. et al, 2022 ), and increasing evidence have demonstrated its role in the pathogenesis of epilepsy ( Vezzani et al, 2019 ; Kumar et al, 2022 ). Using single-cell cellular indexing of transcriptomes and epitopes by sequencing (CITE-seq) techniques, Kumar et al (2022) uncovered a pro-inflammatory microenvironment in the brain lesions of epileptic patients, including an extensive activation of microglia and an infiltration of other pro-inflammatory immune cells, together with a direct interaction between T cells and microglia.…”
Section: Role Of Long Non-coding Rnas In the Progress Of Epilepsy And...mentioning
confidence: 99%
“…Using single-cell cellular indexing of transcriptomes and epitopes by sequencing (CITE-seq) techniques, Kumar et al (2022) uncovered a pro-inflammatory microenvironment in the brain lesions of epileptic patients, including an extensive activation of microglia and an infiltration of other pro-inflammatory immune cells, together with a direct interaction between T cells and microglia. It is well known that activated microglia and astrocytes could interact with surrounding cells by secreting inflammatory factors, promoting neuroinflammatory responses into a vicious circle ( Ginhoux et al, 2010 ; Tian et al, 2012 ; Santiago et al, 2017 ; Fang et al, 2020 ; Liu S. et al, 2022 ). Through microarray screening, Sun et al (2017) identified that LncRNA GAS5 could regulate the polarization of microglia, acting as an epigenetic regulator.…”
Section: Role Of Long Non-coding Rnas In the Progress Of Epilepsy And...mentioning
confidence: 99%